IPTEKS BAGI MASYARAKAT PELAKU USAHA PEMBUATAN PRODUK OLAHAN TANAMAN LIDAH BUAYA (UKM BAROKAH DAN UKM ANUGRAH) DI KEC. RASAU JAYA, KAB. KUBU RAYA, KALIMANTAN BARAT - Samsuddin Samsuddin; Santi Mayda (Jurnal Buletin Al-Ribaath, 2017)
Aloe vera is one of the typical plants in West Kalimantan, and the plant is only able to live in the earthy peat area. Kubu Raya as one of the new regency in Kalimantan Barat, has a lot of wealth potential areas that could be developed, one of the aloe vera plant. However, as the new district, of course it limits its capacity to support the development processed foods product based on aloe vera, so it is needed for cooperation with other parties that can help businesses of processed products maker existing aloe vera plant. During this time the problems for development Aloe vera plant is the limited access to capital and difficult to market processed products. Therefore, through Ipteks bagi Masyarakat (IbM) program with Kemenristekdikti and Muhammadiyah Pontianak University initiative to provide help and assistance, especially in terms of managerial group finance businesses to be bankable to get into banking, and also assist in the management of marketing the product to marketing problems that have been encountered can be resolved.The method used in this IbM activities consist of a number of methods including lectures, practice methods and mentoring, as well as participatory methods and simulation. In this activity the management consulting and guidance to businesses, especially related to the problems they face in the management of business such as marketing development, limited access to capital, including the preparation of business bookkeeping. It aims to provide advice and feedback for performance improvement group of business actors processed Aloe vera plant itself in managing its business. Keywords: Plant Aloe Vera, processed foods, mentoring